The Impact of Fe-Mg Inoculation with Nickel Addition on the Microstructure of Thin-Walled Ductile Cast Iron - Agus Yulianto; Agus Dwi Anggono; Patna Partono; Ngafwan (Engineering Proceedings)
High-temperature-resistant materials, such as stainless steel and cast steel, are widely used in industrial applications. While cast steel has a lower casting ability, cast iron demonstrates a superior casting performance but suffers from structural instability in thin sections, in which its phase structure tends to shift from graphite to cementite. This limits its applicability in thin-walled components. This study aims to characterize thin-walled ductile cast iron with improved high-temperature resistance. The focus is on evaluating the effects of Fe-Mg inoculation with the addition of nickel on the microstructure and mechanical properties of the material. Gray cast iron was cast and inoculated with Fe-Mg and nickel. Mold designs incorporated thickness variations of two, three, four, and five mm. Chemical composition testing was performed in the liquid state using a CE meter and in the solid state using a spectrometer, following ASTM A536 standards for ductile cast iron. A microstructural analysis was conducted using a scanning electron microscope (SEM) JEOL JSM-IT500 SEM (JEOL Ltd., Tokyo, Japan), and hardness was measured using the Vickers method. The results demonstrated that Fe-Mg inoculation with the nickel addition improved the microstructure and hardness of the thin-walled ductile cast iron. These enhancements contribute to increased high-temperature resistance and structural integrity, providing significant benefits for industrial casting processes. The findings have implications for improving the quality of small and medium industry (SMI) products, including the development of advanced metal molds.